(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The possibility of improving the physicochemical and physico-mechanical properties of silicate materials obtained based on lime-belite binder systems and dune sands, for the first time was revealed in the article. Regulation of the hydration processes of structure-formation of lime-belite binder systems with local mineral microfillers under normal and hydrothermal conditions and the dosages of fillers were determined; the mechanisms of their action were explained.